IGF-1 and IGFBP-3 levels in Patients with non-Hodgkin’s Lymphoma - Keleş, Mustafa; Gündoğdu, Mehmet; Erdem, Fuat; Türkeli, Mehmet; Yıldız, Leyla; Turhan, Hamdullah (Fırat University, 2006)
Objectives: Insulin-like growth factor 1 (IGF-1) is an important growth and anti-apoptotic factor for the cancer cells in several malignancies. IGF binding protein-3 (IGFBP-3) also apparently inhibits growth and induces apoptosis through IGF-independent mechanisms. In this study it was aimed to measure serum IGF-1 and IGFBP-3 levels in 25 patients with non-Hodgkin’s lymphoma and to compare with these results to healthy controls, and it was also aimed association between these results and some prognostic factors. Materials and Methods: Twenty five patients with non-Hodgkin’s lymphoma (NHL) whose age ranging from 18-63 (mean ± SE 40 ± 16.19) and 25 healthy volunteer whose age ranging from 18 to 63 (mean ± SE 40 ± 16.27) were obtained in Hematology and Oncology Department. Blood samples were collected and separated serums stored in –800C until study. IGF-1 ve IGFBP-3 levels were measured with immunofluorescence assay (IFA) and immunoradiometric assay (IRMA) (respectively). Results: IGF-1 level was higher in patients with NHL (mean±SE;357.88±197.45 ng/ml) than in healthy volunteer group (332.47±140.51 ng/ml), but this difference was not statistically significance (p>0.05). IGFBP-3 level was lower in patients with NHL (mean±SE; 1753.14±603.58 ng/ml) than in healthy volunteer group (1842.84±403.33 ng/ml), but this difference was not statistically significance (p>0.05). IGFBP-3 level in patients with B symptoms (1577.35±582.52 ng/ml) was significantly lower than in patients without B symptoms (2065.66±533.86 ng/ml) (p

Amaç: İnsülin benzeri büyüme faktörü (IGF), bir çok kanser türünde kanser hücreleri için önemli bir büyüme ve antiapopitotik faktördür. İnsülin benzeri büyüme faktörü bağlayıcı protein-3 (IGFBP-3) ise IGF-1 den bağımsız apopitozisi uyarır ve büyümeyi inhibe eder. Bu çalışmada serum IGF- 1 ve IGFBP-3 düzeylerine bakmayı, sağlıklı kontrol ile karşılaştırmayı ve bazı prognostik faktörlerle ilişkilerini araştırmayı amaçladık. Gereç ve Yöntem: Hematoloji ve Onkoloji Bilim Dallarında non Hodgkin lenfoma (NHL) tanısı konan ve yaşları 18-63 (ortalama 40±16.19) arasında olan 25 olgu ile, 18-63 yaşları arasında olan 25 sağlıklı gönüllüden 8-10 ml venöz kan alındı. Santrifüj edilen kanların serumları ayrılarak çalışma gününe kadar -800C de derin dondurucuda bekletildi. Hasta ve kontrol serumlarından IGF-1 ve IGFBP-3 ölçümleri immunoflorasan assay (IFA) ve immunoradyometrik assay (IRMA) yöntemleri ile yapıldı. Bulgular: Hasta grubunun serum IGF-I düzeyi (357.88±197.45 ng/ml) kontrol grubuna (332.47±140.51 ng/ml) göre yüksek olmasına rağmen bu fark istatistiksel olarak anlamlı değildi (p>0.05). Hasta grubunun IGFBP-3 (1753.14±603.58 ng/ml) düzeyleri kontrol grubuna (1842.84±403.33 ng/ml) göre düşük olmasına rağmen bu fark da istatistiksel olarak anlamlı değildi (p>0.05). IGFBP-3 düzeyi B semptomu olan hastalarda (1577.35±582.52 ng/ml) B semptomu olmayanlara(2065.66±533.86 ng/ml) göre daha düşük olarak bulundu (p
Non-Hodgkin Lenfomalı Hastalarda IGF-1 ve IGFBP-3 Düzeyleri